Pengaruh Service Quality dan Brand Trust Terhadap Customer Satisfaction Pada Travel Umrah & Haji Sahabat Zamzam Indonesia (Studi Pada Jamaah Travel Umrah dan Haji Sahabat Zamzam Indonesia) - Shella Dinda Septiana; Farida Akbarina (Indonesia Economic Journal, 2025)
Service quality and brand trust are key factors influencing customer satisfaction, especially in service-based industries like Umrah and Hajj travel. This study focuses on Sahabat Zamzam Indonesia, a travel provider in Lumajang Regency, aiming to analyze how these two variables affect customer satisfaction among its pilgrims. Using a quantitative explanatory method, the research involved 100 respondents who had previously performed Umrah with the company. Data collection was conducted through questionnaires, and analysis included descriptive statistics, classical assumption testing, multiple regression, and hypothesis testing. The findings reveal that both service quality and brand trust have a positive and significant partial effect on customer satisfaction. The regression results show an F-count greater than the F-table and a coefficient of determination (R²) of 0.917, indicating that 91% of customer satisfaction is influenced by the two independent variables, while the remaining 8.3% is attributed to other unexamined factors. This implies that enhancing service quality and strengthening brand trust play a critical role in improving customer satisfaction. Therefore, Sahabat Zamzam Indonesia is advised to maintain consistent service delivery and reinforce brand trust through professionalism, transparency, and a strong commitment to the quality of its worship programs.